Estimation of Arabian rigid plate motion and strain rate accumulation within the Arabian plate using GPS measurements - Almuslmani, Bandar Saleh (2010)
The Arabian plate is classified as medium sized. It is surrounded by the Nubian, Somalian, Eurasian and Indian plates. Previous investigations of present-day kinematics of the Arabian plate using GPS measurements were primarily obtained from stations located on surrounding plates, with few stations actually located on the Arabian plate itself. Due to the inhomogeneous distribution of these GPS stations and the fact that some of these were actually located in the plate boundary zone, the motion of Arabia was only sensed in a few locations of the rigid plate interior.